GAMBARAN TINGKAT PENGETAHUAN IBU TENTANG PEMILIHAN KONTRASEPSI DI PUSKESMAS JAGIR SURABAYA - Ethyca sari (Jurnal Keperawatan, 2014)
Contraception is to avoid or prevent the occurrence of pregnancy as a result of a meeting between a mature egg with the sperm. Lack of knowledge mother - the mother in choosing a contraceptive barrier contraceptives in the management of elections. Several factors influence the level of knowledge among age, education, occupation, socioeconomic and experience. If the mother's knowledge about contraception less enormous influence, for example if the mother does not use contraception has been in the family planning services can result in pregnancy. The purpose of this study was to obtain an overview of the level of knowledge mother in choosing contraception in Puskesmas Jagir Surabaya. This research is descriptive. Sampling taken at consecutive sampling with a sample population of 27 mothers and 26 mothers who follow the KB at Puskesmas Jagir Surabaya. Intake of processed data through questionnaires in the form of tabulation. Variable in this study is the level of mothers' knowledge of contraception in health centers elections Jagir Surabaya. The results showed a good level of knowledge mother as many as 15 people (57.7%), while as many as 6 people (23%), and less than 5 people (19.3%). Can be drawn from these studies that the level of knowledge of good mothers. Suggestions to improve the knowledge about contraception counseling conducted by the health worker or midwife in the nearest health center. most of the mothers had good knowledge, this was due to the many education and information regarding the direct and indirect both government and non-government, and in general they get the information from visual and electronic media have received adequate information from the existing cadre KB nearest health center.